LOLITA: TAJWEED GAME-BASED LEARNING MEDIA DEVELOPMENT USING THE HANNAFIN AND PECK MODEL - Nazliati, Nazliati; Nurhanifah, Nurhanifah; Sari, Rita; Alfiatunnur, Alfiatunnur (Jurnal Ilmiah Didaktika, 2024)
Tajweed is the science of reading the Qur'an, which is urgently taught to students to avoid mistakes when reading or reciting it. However, learning tajweed is quite complicated. Game-based learning media are very suitable for development, especially for students at the concrete operational stage, to facilitate understanding of tajwid. Therefore, this study was conducted to develop Ludo Lintas Tajweed (Lolita) using the Hannafin and Peck model, which consists of three phases: analysis, design, and development/implementation. The model also emphasizes an iterative approach, which is essential to ensure that the product or program developed meets users' needs and effectively achieves them. Descriptive analysis was conducted to describe each phase of media development, while percentage analysis was carried out to analyze the media validation from the subject experts and students' responses. The results showed that the development process of Lolita, a game-based learning media, has been in accordance with the Hannafin and Peck phase and is feasible to develop with media validation (88%), content validation (90.7%), language validation (80%), small group validation (100%), and large group validation (98.5%).